Osthole inhibits the migration and invasion of highly metastatic breast cancer cells by suppressing ITGα3/ ITGβ5 signaling - Chen Yue-qiang; Song Hai-yan; Zhou Zhong-yan; Ma Jiao; Luo Zhan-yang; Zhou Ying; Wang Jian-yi; Liu Sheng; Han Xiang-hui (Acta Pharmacologica Sinica, 2022)
Metastasis is the leading cause of death in breast cancer patients. Osthole, as an active compound detected in the traditional Chinese medicine Wenshen Zhuanggu Formula, has shown a promising anti-metastatic activity in human breast cancer cells, but the underlying mechanisms remain ambiguous. In this study we elucidated the anti-metastatic mechanisms of osthole in highly metastatic breast cancer cells and a zebrafish xenograft model. We showed that the expression of integrin α3 (ITGα3) and integrin β5 (ITGβ5) was upregulated in highly metastatic MDA-MB-231, MDA-MB-231BO breast cancer cell lines but was downregulated in poorly metastatic MCF-7 breast cancer cell line, which might be the key targets of osthole’s anti-metastatic action. Furthermore, we showed that knockdown of ITGα3 and ITGβ5 attenuated breast cancer cell migration and invasion possibly via suppression of FAK/ Src/Rac1 pathway, whereas overexpression of ITGα3 and ITGβ5 caused the opposite effects. Consistently, osthole significantly inhibited breast cancer metastasis by downregulating ITGα3/ITGβ5 signaling in vitro and in vivo. These results provide new evidence that osthole may be developed as a candidate therapeutic drug for metastatic breast cancer.